Trace elements in fish species from the Punjnad headworks: Bioaccumulation and human health risk assessment. - Saima Naz; Qudrat Ullah; Dalia Fouad; Abdul Qadeer; Maria Lateef; Muhammad Waqar Hassan; Ahmad Manan Mustafa Chatha (PLoS ONE)
Aquatic toxicology, as a result of industrial and agrieqcultural effluences, has become a global concern impacting not only the well-being of aquatic organisms but human health as well. The current study evaluated the impact of four toxic trace elements (TTEs) Cadmium (Cd), copper (Cu), lead (Pb), and nickel (Ni) in three organs (liver, gills, and muscles) of five fish species viz, Rita rita, Sperata sarwari, Wallago attu, Mastacembelus armatus, and Cirrhinus mrigala collected from right and left banks of Punjnad headworks during winter, spring, and summer. We investigated the accumulation (mg/kg) of these TTEs in fish in addition to the human health risk assessment. The obtained results showed that W. attu accumulated significantly more TTEs (p < 0.00) as compared to other fish. Among seasons, summer had significantly more (p < 0.00) accumulation of TTEs than other seasons. Lead (Pb) accumulation was highest across TTEs in fish liver as compared to gills and muscles. The right bank showed higher accumulation (p < 0.00) of all TTEs in all fish species compared to the left bank. The human health risk assessment showed that Cd and Pb had higher exposure levels than Cu and Ni. Furthermore, the THQ was in the order of Cd > Pb > Ni > Cu. All fish species had THQ 1 for Cd and Pb and TTHQ > 1 for all fish. MPI index showed moderate to high levels of TTE contamination in all fish species. The study concluded that the right bank has higher metal accumulation than the left bank. However, fish consumption from both study sites was unsafe for human consumption. Further studies are required to evaluate the contamination of other trace elements in the aquatic ecosystem of the current site. This study will be useful for policymakers and the water department to take necessary counteractions to reduce the impact of TTEs at the study site.